Influence of Zr substitution on structure, electrical and magnetic properties of Bi0.9Ho0.1FeO3 ceramics - Guannan Li; Haoting Zhao; Ruxia Yang; Jianfeng Tang; Chunmei Li; Yuming Lu (Results in Physics, 2019)
Polycrystalline Bi0.9Ho0.1Fe1-xZrxO3 ceramics have been synthesized by standard solid state sintering method. The influences of Zr doping on structure, dielectric, ferroelectric and magnetic properties were investigated. The results of the XRD patterns suggest that all the samples have a rhombohedral structure (space group R3c). Structure refinement of the XRD patterns shows that the lattice parameters are increased as the Zr4+ concentration increasing. The average grain size of the samples decreases with Zr doping due to the suppressed of grain growth caused by Zr substitution. The dielectric loss is reduced and the remnant polarization (Pr) is decreased with increasing Zr concentration. As Zr doping level increases, the weak ferromagnetism becomes more obvious, and the remnant magnetization gradually increases and reaches the maximum value at x = 0.04. Keywords: Multiferroic materials, Ferroelectric, Ferromagnetic, Bismuth ferrite